Efektifitas Senam Kaki Diabetik terhadap Ankle Brachial Index pada Pasien Diabetes Melitus: Literature Review - Nuriya; Agis Taufik (Journal of Bionursing, 2022)
Diabetes mellitus is known as "the silent killer" because it can affect all body organs and cause complications, including complications in the feet. These complications can increase the rate of amputations and are life-threatening. Prevention can be done by doing foot exercises. In principle, leg exercises are done by moving all the joints of the legs to improve blood circulation. Blood circulation in the leg area can be measured through the Ankle Brachial Index examination. This study was to identify the effectiveness of diabetic foot exercise. The article search begins with conducting a PICO analysis, then continues with an electronic search for articles using Google Scholar, the year the article was published from 2016 to 2020. The keywords used are "Diabetes Mellitus" and "Leg exercise.” Screening is carried out through inclusion and exclusion criteria to determine the articles to be reviewed. So that articles were obtained that matched the inclusion criteria for review. Results showed nursing interventions for foot exercise on the ankle-brachial index in patients with type II Diabetes Mellitus can be categorized as safe and effective interventions that are given five times a week or for 30 minutes for 5 days or 6x2 a week to reduce the risk of injury to the ankle. foot. Performing effective foot exercises can increase the value of the Ankle Brachial Index to normal. 30-minute foot exercise for 5 days or 6x2 a week should be promoted and implemented as a routine to reduce the risk of injury in patients with diabetes mellitus. In conclusion, foot exercise in type II DM patients can increase the Ankle Brachial Index value which tends to be low to normal.